Analysis of Implementation of Electronic-based Parking Retributions (E-Parking) to Medan City Regional Revenue - Sulystio, Kelvin (Al-Muhtarifin: Islamic Banking and Islamic Economic Journal, 2024)
Parking fees are one of the regional sources of income from the regional tax. The purpose of this study is to analyze the regional revenue generated from the regional tax, known as Electronic Parking Fee or E-Parkir. The methodology in this study uses qualitative descriptive methods in the form of written and tabular data. The data source for this study comes from interviews with transport departments and users of e-parking systems. The results of this research show that the implementation of e-parking or e-parking will use digital payment systems such as e-payment cards and QRIS implemented at several road points in Medan city. The conclusion of the implementation of e-parking in Medan city is that the data proves that the implementation of e-parking can increase the local revenue. The implementation of e-parking in Medan City has no obstacle in terms of revenue because the city government and third parties have a benefit distribution mechanism, so in terms of local revenue, Medan City will increase, although this cannot be denied. There are obstacles on the ground, e-parking users and e-parking attendants are still dealing with cash transactions.